2020
DOI: 10.1111/sjop.12668
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self‐harm and alexithymia: A systematic review and meta‐analysis

Abstract: Self-harm, defined for the purpose of this review as any act of self-injury without explicit suicidal intent, is an increasing public health concern, with potential long-term implications for those who engage in it. Previous research has identified a correlational relationship between self-harm and alexithymia, an emotion processing deficit characterized by difficulties identifying and describing feelings, and an externally orientated thinking style. Through a systematic search of the literature, the current r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 121 publications
2
22
0
Order By: Relevance
“…This has made it possible to substantiate the observation that alexithymia is related with psychosomatic diseases. Moreover, alexithymic characteristics were found in various clinical conditions characterized by a disordered affect regulation (5), such as depression (16), self-harm and suicidality (17)(18)(19), schizophrenia (20), eating disorders (21,22), substance use disorder (23) and autism spectrum disorder (24,25). Hence, alexithymia started to be considered a non-specific vulnerability factor involved in the development of physical and mental disorders as well as a specifier associated with adverse outcomes when treating such conditions [see e.g., (26,27)].…”
Section: Introductionmentioning
confidence: 99%
“…This has made it possible to substantiate the observation that alexithymia is related with psychosomatic diseases. Moreover, alexithymic characteristics were found in various clinical conditions characterized by a disordered affect regulation (5), such as depression (16), self-harm and suicidality (17)(18)(19), schizophrenia (20), eating disorders (21,22), substance use disorder (23) and autism spectrum disorder (24,25). Hence, alexithymia started to be considered a non-specific vulnerability factor involved in the development of physical and mental disorders as well as a specifier associated with adverse outcomes when treating such conditions [see e.g., (26,27)].…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis by Norman et al. (2020) suggested that alexithymia is moderately associated with NSSI, and the relationship was more significant in women than in men. This study also speculated that the association between alexithymia and NSSI might be due in part to poor emotion regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this peculiarity, alexithymia is thought to adversely impact nursing students' communication skills (Sancar & Aktas, 2019). There is increasing recognition that poor emotion regulation is a core process underlying alexithymia (Norman et al., 2020). Evidence suggests that people with alexithymia usually adopt more suppression and choose fewer reappraisal strategies (J. Chen et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the review concluded that there might be evidence of clinical variables, particularly depression, impacting the relationship between alexithymia and suicide ideation and behavior. Other meta-analyses have found a medium effect size for the relationship between alexithymia and self-harm outcomes, and have again found the subcomponents of difficulty identifying and describing feelings to be strongest correlates ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 89%